2012
DOI: 10.1210/jc.2011-3296
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and Fetal IGF-I and IGF-II Levels, Fetal Growth, and Gestational Diabetes

Abstract: Higher maternal IGF-I (but not IGF-II) levels at mid- and late gestation may indicate greater placental and fetal growth. IGF-I (but not IGF-II) may be implicated in fetal hypertrophy in gestational diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
62
4
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(75 citation statements)
references
References 31 publications
8
62
4
1
Order By: Relevance
“…One study showed that IGF-2 levels were higher in cord serum of offspring of diabetic mothers but did not correlate with birth weight [46]. Another showed that cord blood IGF-2 levels did not vary between mothers with and without diabetes but that IGF-2 was weakly correlated with birth weight and placental weight [47]. Both studies found a positive relationship between IGF-1 and birth weight and that infants of diabetic mothers had greater IGF-1 levels [46,47].…”
Section: Studies Examining Igf-2 Weight and Adipositymentioning
confidence: 99%
“…One study showed that IGF-2 levels were higher in cord serum of offspring of diabetic mothers but did not correlate with birth weight [46]. Another showed that cord blood IGF-2 levels did not vary between mothers with and without diabetes but that IGF-2 was weakly correlated with birth weight and placental weight [47]. Both studies found a positive relationship between IGF-1 and birth weight and that infants of diabetic mothers had greater IGF-1 levels [46,47].…”
Section: Studies Examining Igf-2 Weight and Adipositymentioning
confidence: 99%
“…Although the values of IGF-1 did not differ in mothers with DM (T1DM and T2DM) and normal mothers before and throughout pregnancy, IGF-1 concentration in cord serum of offspring born to diabetic mothers were significantly higher than of those of normal mothers [33]. Luo et al have shown that maternal and fetal IGF-1 levels were significantly higher in gestational diabetic than in nondiabetic pregnancies and that higher maternal at mid and late gestation appear strongly predictive of LGA birth [34]. Insulin growth factor-1 regulates amino acids transport in the placenta.…”
Section: Potential Mechanisms For Excessive Fetal Growthmentioning
confidence: 99%
“…Increased levels of IGF-1 contribute to the upregulation of placental amino-acid transporters resulting in elevated fetal amino acid levels in GDM [35]. Nevertheless, the association between maternal levels of IGF-1 and size at birth are inconsistent [34,[36][37][38]. It has been shown that cord blood IGF-1 levels are higher in LGA infants than in the AGA infants of non diabetic mothers [36] and high IGF-I levels are related to insulin resistance [39].…”
Section: Potential Mechanisms For Excessive Fetal Growthmentioning
confidence: 99%
“…10 On the other hand, IGF-I levels (but not IGF-II) are higher in fetuses with weights above the mean for gestational age. 11 IGF-binding proteins (IGFBPs) are inhibitors of IGF actions on metabolism and growth. 12 Currently, there are six named IGFBPs that can complex with both IGF-I and IGF-II.…”
Section: Introductionmentioning
confidence: 99%